Metaphysics - Van Inwagen, Peter (Boulder, San Francisco, Westview Press, 1993)
Accepting the traditional definition of metaphysics as the study of ultimate reality, Peter van Inwagen builds this strikingly original textbook around three crucial questions: What are the most general features of the world? Why does the world exist? And what is the nature and place of rational beings in the world?In the informal but precise style for which he is known, van Inwagen surveys the classical answers to these questions while teaching his readers through example how to think about them more clearly and deeply on their own. By the end of the book, he has introduced most of the perennial topics of metaphysics, including appearance and reality, identity and individuation, objectivity, necessary existence, mind and body, teleology, and freedom of the will. Engaging and provocative, but always fair and reasonable, Metaphysics provides both a lucid guide to the study of First Questions and a paradigm of philosophical exposition. It will immediately take its place at the forefront of leading contemporary texts on metaphysics
pt. 1. The way the world is. Individuality ; Externality ; Objectivity -- pt. 2. Why the world is. Necessary being : the ontological argument ; Necessary being : the cosmological argument -- pt. 3. The inhabitants of the world. What rational beings are there? ; The place of rational beings in the world : design and purpose ; The nature of rational beings : dualism and physicalism ; The nature of rational beings : dualism and personal identity ; The powers of rational beings : freedom of the will ; Concluding meditation
Includes bibliographical references (pages 215-216) and index
Keywords: Metaphysics